2014
DOI: 10.1517/14728222.2014.900045
|View full text |Cite
|
Sign up to set email alerts
|

The high mobility group A1 molecular switch: turning on cancer – can we turn it off?

Abstract: Introduction Emerging evidence demonstrates that the high mobility group A1 (HMGA1) chromatin remodeling protein is a key molecular switch required by cancer cells for tumor progression and a poorly differentiated, stem-like state. Because the HMGA1 gene and proteins are expressed at high levels in all aggressive tumors studied to date, research is needed to determine how to ‘turn off’ this master regulatory switch in cancer. Areas covered In this review, we describe prior studies that underscore the central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 105 publications
0
37
0
Order By: Relevance
“…Significantly represented networks featured proteins previously implicated in ERMS biology such as Cyclin D1, IGF, AKT, SP1, and CDKN2A3536373839. Network analysis also suggested target proteins that, though not previously studied in RMS, have been implicated in other tumor types with roles in cell proliferation such as NFYB40, invasion and metastasis such as YBX141, and cellular transformation such as HMGA142. The findings of protein nodes previously implicated in ERMS biology supports the role of exosomes as mediators of such pathway alterations, while the findings of novel cancer-associated protein networks opens possibilities for investigation of such pathways in ERMS tumors.…”
Section: Discussionmentioning
confidence: 88%
“…Significantly represented networks featured proteins previously implicated in ERMS biology such as Cyclin D1, IGF, AKT, SP1, and CDKN2A3536373839. Network analysis also suggested target proteins that, though not previously studied in RMS, have been implicated in other tumor types with roles in cell proliferation such as NFYB40, invasion and metastasis such as YBX141, and cellular transformation such as HMGA142. The findings of protein nodes previously implicated in ERMS biology supports the role of exosomes as mediators of such pathway alterations, while the findings of novel cancer-associated protein networks opens possibilities for investigation of such pathways in ERMS tumors.…”
Section: Discussionmentioning
confidence: 88%
“…The ultimate goal of further work in this field is to identify therapeutic strategies to target HMGA1 in human cancer [reviewed in reference 282]. While many studies cited here underscore the fundamental role of HMGA1 in tumor progression, there has been relatively little work focused on targeting HMGA1 in cancer [176].…”
Section: Resultsmentioning
confidence: 99%
“…HMGA1 is also enriched in human embryonic stem cells [58, 97, 98], adult stem cells, such as hematopoietic stem cells [96, 97], intestinal stem cells [120], and high-grade or poorly differentiated tumors [27, 281, 282], suggesting that it plays a role in driving the undifferentiated, stem-like state. In addition, its high expression during embryogenesis with absent or markedly decreased levels in differentiated, adult tissues further implicates HMGA1 in enforcing a stem-like state [98].…”
Section: Areas For Future Investigationmentioning
confidence: 99%
“…18 Small intestinal tissue was used because we previously reported that Hmga1 transgenics develop marked proliferative changes and polyposis that involves both the small 21 intestine and colon, although polyposis was most pronounced in the small intestine. 18 We also investigated human CRC tumor and matched, adjacent non-neoplastic tissue from colonic biopsies obtained at colonoscopy.…”
Section: Samples and Metabolite Extractionmentioning
confidence: 99%
“…Gene expression profile analyses demonstrate that HMGA1 drives tumor progression and stem cell properties through transcriptional networks expressed in pluripotent stem cells and developing embryos. 18,[21][22][23] Recently, the metabolic profiles of primary CR tumors and adjacent, nonmalignant tissue have been examined using several techniques, including: magic angle spinning -nuclear magnetic resonance (MAS-NMR), gas chromatography -mass spectrometry (GC-MS), ultra-performance liquid chromatography -quadrupole time-of-flight mass spectrometry (UPLC-QToF-MS) and capillary electrophoresis -MS (CE-MS). [24][25][26][27][28][29][30][31][32][33][34] Other platforms used to investigate metabolomes from urine or serum of patients with CRC include GC-MS, UPLC-QToF-MS (MS/MS), Fourier transform ion-cyclotron-MS (FTICR-MS) and proton NMR ( 1 H-NMR).…”
Section: Introductionmentioning
confidence: 99%